(3GQJTGa GdVQH aj dSGf GdYQHs - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf,J (B745 (3g` s ((3YGeQ Hf MSf GdTGPdi GdCRgQi s)
(3ChdgG (B:s
(3bGd SjOfG CKjQ GdOjf CHh MjGf GdMeO ddg QH GdYGdejf CeG HYO aEf Yde GdfMh UYH GdeQGe hMUQJg ai LedJjf GdChdi ai CMcGe Gdcde bHd GdJQcjH GdKGfjI ai CMcGegG MGdI GdJQcjH s
(3BNQgG (B:s
(3hCeG Gdchajhf adjSJ CSekG Hd SGOI hGddg CYde fLR GdLRA GdKGfi ef cJGH EQJTGa GdVQH ef dSGf GdYQH HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B130s
Keywords: (3GdfMhs